Notas sobre as tecnologias de cartografia - algumas implantações para o urbanismo das cidades coloniais no Brasil - Gunn, Philip (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2000)
This paper deals with cartographic imprécisions which add to others found in the first registers of the 16th century about life in the new South American colonies. The introduction shows historical, geographical and representational inaccuracies concerning the Indian settlements in the area of present-day state of São Paulo. In the second part, issues of cartographic techniques are discussed in relation to problems of misun derstn ding navigational instruments, such as that of reading the "needle direction" attention being especially paid to the imprecision of longitudinal measurement. In the third part, evidences of the difficulties in determining longitude are collected in cartographical interpretation disputes between Portugal and Spain up to 1750. At that time , longitudinal imprecision in maps and geopolitical interests were combined. The conclusion shows that it was for that reason that power of colonial administration was based on the urban form s of territorial occupation, which changed after 1750 a ccording to the new colonial interests